Place of Psychotherapy in Psychology Movement Toward Cognitivism - Todorović, Milorad V (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
Psychology striving to make us more aware of our own nature dominantly, if not exclusively, is realized through psychotherapy. Psychotherapy as a praxis of psychology, which only follows the psychological theory and without it we can hardly call it that, is largely dependent on the prevailing social trends and the dominant form of pathology that can occur in them. That theoretical aspects of many forms of pathology are not completely understood and not give the right to cancel the search for the unconscious forces that determine the subject. Dominant tendencies in contemporary psychology not only do not favor psychotherapy, but are directly aimed against it. At least against that psychotherapy which is based on the split subject, the interior space in which the physical and perceptual sensations, moral rules, mood depression and everything else that we call "mental". The great danger that is above psychotherapy activity comes by pharmacology and cognitivism (lat. Cognitio - "knowledge") and the intellectual soul. Equating the mind and the brain makes psychotherapy unnecessary in relation to the pharmacology whose power impact becomes decisive on each deviation and every suffering. The fact that in the psychology shortens the long and uncertain path of mental knowledge that does not correspond to the nature of "psychological" seems to be replaced by those efforts which are only concerned with the question of science. The fact that there is no comprehensive theory of emotions that can not be resolved by cognitivism which is opposite to emotional. Rorty`s cynicism towards such efforts, which emphasize that the spirit is the same as that stimulate the brain and that the theorem symphonies and excreted in the same way that the spleen is excreted dark juices (Rorty 1990: 54) exhorts the psychology of the fact that instead of being which has a spirit, that is different from the "physical body", "matter", the central nervous system, has been the equalization of the spirit with this case of positivist science study. Consciousness, which turns psychology, becomes infinite, and non spatial, or possession of a non spatial bodies or elements almost disappears. The most controversial consequence of this is that possessing inner life is not relevant for understanding. Dynamic psychology is targeted by those who want to replace it with chemical treatment, which is more effective than psychotherapy because it affects cerebral causes of strife and suffering. Passion, death, madness, unconsciousness, sexuality, object relations, which shape each subjectivity, in such a psychology will be made redundant, or will be, like previous experiences, translate into the language of the new psychological school. However, the survival of the unconscious in psychological theory, the unique psychological theory, psychotherapy life will depend on the ability that man, freeing of the self-deception, reach his freedom.